Electrochemical Detection of Iron in a Lixiviant Solution of Polluted Soil Using a Modified Glassy Carbon Electrode. (16th January 2012) - Anguiano, D. I.; García, M. G.; Ruíz, C.; Torres, J.; Alonso-Lemus, I.; Alvarez-Contreras, L.; Verde-Gómez, Y.; Bustos, E.
Abstract : This paper presents preliminary results on the modification of glassy carbon electrodes with Multiwall Carbon Nanotubes with or without Polyaniline and Pt nanoparticles as electrocatalytic materials for metallic pollutants detection. Electrodes were constructed and incorporated as amperometric detectors of ionic iron electroreduction using the Flow Injection Amperometric technique in aqueous solution. The results not only revealed the modified electrode with nanotubes, polyaniline and platinum nanoparticles were the most selective and sensitive, but also provided an electroanalytic tool to analyze iron in lixiviated samples of polluted soil. The proposed iron sensor exhibited a linear response between 0 and 10 mM with detection and quantification limits of 0.003 and 0.012 μ M, respectively. The aqueous samples were taken from a lixiviated solution of polluted soil from Mineral de Pozos, Guanajuato, Mexico, to define the erosion grade of soil.